2010
DOI: 10.1016/j.ahj.2009.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Management patterns of non-ST segment elevation acute coronary syndromes in relation to prior coronary revascularization

Abstract: The NSTE-ACS patients with previous PCI were more likely to be treated invasively. Conversely, patients with prior CABG less frequently received invasive therapy. Future studies should determine the appropriateness of this treatment discrepancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 39 publications
1
17
0
1
Order By: Relevance
“…Previous studies from the 1990s 13 and the 2000s 6,9 have suggested that patients with prior bypass surgery have an increased in-hospital mortality, which was likely because of more adverse baseline characteristics in the post-CABG cohort. Our data seem to be in agreement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies from the 1990s 13 and the 2000s 6,9 have suggested that patients with prior bypass surgery have an increased in-hospital mortality, which was likely because of more adverse baseline characteristics in the post-CABG cohort. Our data seem to be in agreement.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Therefore it has been hypothesized that a prior CABG could exert a protective effect, as a result of the double coronary circulation and ischemic preconditioning. 6,9,10 The purpose of this meta-analysis was to systematically review and synthesize existing data on prognosis of patients with ACS and a history of a previous CABG, with respect to in-hospital, short-term and long-term outcomes.…”
mentioning
confidence: 99%
“…15 Patients with recurrent angina after CABG are usually elderly and co-morbid health problems are very common. [16][17][18] Redo CABG is uncommon and only performed in o2% of invasively managed acute coronary syndrome patients. 17 In the United Kingdom, of 161 patients who had PCI 126±65 months after CABG, cardiac death, myocardial infarction or repeat PCI occurred in 14% of them by 13 months (mainly related to repeat PCI (12%)).…”
Section: Clinical Use Of Autologous Saphenous Veinmentioning
confidence: 99%
“…[16][17][18] Redo CABG is uncommon and only performed in o2% of invasively managed acute coronary syndrome patients. 17 In the United Kingdom, of 161 patients who had PCI 126±65 months after CABG, cardiac death, myocardial infarction or repeat PCI occurred in 14% of them by 13 months (mainly related to repeat PCI (12%)). In the United Kingdom overall, of the 33 652 PCIs performed in 1999/2000, 907 (2.7%) occurred in patients with prior CABG.…”
Section: Clinical Use Of Autologous Saphenous Veinmentioning
confidence: 99%
“…[205] Compared to patient without prior CABG, patients with prior CABG presenting with ACS are older, have more cardiovascular risk factors, more frequent comorbidities, higher TIMI risk score, lower left ventricular ejection fraction, had higher prevalence of previous treatment with evidence-based medications, were less likely to have ST-segment deviation or positive cardiac biomarker on presentation. [206][207][208][209] During hospitalization prior CABG patients experienced larger infarct size, were less likely to receive reperfusion therapy, early invasive therapy and were more likely to be managed medically when compared to non-CABG patients. [207,209] However, the efficacy of reperfusion therapy in patients with previous CABG is less well characterized.…”
Section: Antithrombotic Therapy During Graft Intervention -mentioning
confidence: 99%